The correlation between daily fisherman’s demographics and their catching behaviors in Tegal, Indonesia - Nizar Aulia Alharizmi; Fauzan Romadlon; Achmad Zaki Yamani (Institute of Computer Science (IOCS), 2022)
The majority of people in Tegal City work as daily fishermen. However, in the handling process, there are incompatibilities between fish caught quality and wholesaler standards. The causes are lack of experience, knowledge and less training about fish handling. Therefore, it needs to find the correlation between fishermen’s socio-economic (demographic) and their catching behavior. This study uses quantitative methods. The collected data were statistically tested using ANOVA. The results showed income factor has significant correlation with poor fishing technique and fish slime. Departure time has significant correlation with poor fishing technique and wet ice handling. Fish damage percentage has significant correlation with stock of cooling media and fish quality decline. Thise factor is due to the lack of daily fishing capital and catching knowledge. Therefore, it needs cooperation from various parties to facilitate daily fishermen to gain optimal yields.